Performing nature's value: software and the making of Oregon's ecosystem services markets. - Nost, Eric (Environment & Planning A, 2015)
Geographers of technology illustrate software code's contexts, effects, and agencies as they shape urban space and everyday life, but the consequences of code for nature remain understudied. Political ecologists have critiqued remote sensing and Geographic Information Systems (GIS) based conservation projects, but have not engaged more broadly with the role of software in the contested production, circulation, and application of ecological knowledge. Yet, around the world, data analytics firms and conservation nonprofits argue for optimizing environmental management through faster and bigger data collection and new techniques of data manipulation and visualization. I present a case study from the US state of Oregon, illustrating how conservationists and environmental regulators employ computer programming to plan markets in which entrepreneurs restore stream and wetland ecosystem services to earn offset credits. In these markets, code-executed algorithms constituting spreadsheets, web maps, and GIS utilities generate, relate, and make sense of the data that define credit commodities. I argue that code tends toward three effects: producing a landscape defined by wetlands' modeled value, performing social relations associated with nature's neoliberalization and financialization, and legitimating these moves. Although emphasis on the performativity of code and other technological objects is warranted, the contexts in which these are authored, deployed, and evaluated should remain central to understanding environmental governance. This is to caution against seeing technology as reducing nature and society to state or capitalist rationalities and to hesitate to differentiate prima facie code's work on space and on nature. I call for bridging political ecology and geographies of technology in ways that can explain how code is generative of environmental knowledge, change, and conflict.